EFEKTIVITAS PEMBERIAN ORAL HYGIENE + CLOSE SUCTION + HEAD UP 30-45? SEBAGAI BUNDLE PENCEGAHAN VAP (VENTILATOR ASSOCIATED PNEUMONIA) PADA RESPONDEN TN. S DENGAN PENGGUNAAN VENTILATOR MEKANIK DI RUANG ICU RSUP PROF dr. I. G. N. G. NGOERAH BALI - Karina Puspa Wulandari Puspa; Ruris Haristiani; Baskoro Setioputro; Heri Siswanto (Institut Kesehatan Hermina, 2024)
Ventilator Associated Pneumonia or VAP is the occurrence of pneumonia in patients who are mechanically ventilated using an endotracheal tube (ETT) with a minimum duration of use of 48 hours. The incidence of VAP in hospitals can be minimized with a procedure, namely the VAP Bundle. Procedures in VAP Bundle include raising the head of the bed, suctioning tracheal mucus, and oral care with 0.2% chlorhexidine. The purpose of writing Scientific Research is to evaluate the VAP Bundle procedure which nurses can carry out independently as a preventive measure for VAP in the ICU. The technique for collecting respondents in this research is purposive sampling. The materials and instruments used in this research used standard operating procedures (SOP) Oral Hygiene + Close Suction + Head Up 30-45?. Meanwhile, the data collection instrument in the VAP Prevention Bundle is an observation sheet in the form of Clinical Infection Scroe Monitoring (CPIS) to assess the incidence of pneumonia in patients on ventilators. The results of this study showed that the Clinical Pulmonary Infection Score (CPIS) value on the 3rd day and 6th day of using the ventilator showed that the patient's CPIS score was ?6 so that the patient was declared not diagnosed with VAP. VAP Bundle is an appropriate procedure to prevent the occurrence of VAP in the ICU in patients who are installed on a mechanical ventilator. Implementing VAP Bundle can speed up the duration of use of a mechanical ventilator so as to minimize exposure to germs or the emergence of other diseases that can worsen the patient's condition.